PENGARUH PROSES PEMBELAJARAN IPS DAN IKLIM KELUARGA TERHADAP PEMBENTUKAN KARAKTER SISWA DI SMAN 16 PANGKEP - Rudisaberi Rudisaberi; Muh. Yahya; Muh. Sri Yusal (Jurnal Education and Development, 2022)
This study aims to determine: (1) the influence of the social studies learning process on the character building of students at SMAN 16 Pangkep, (2) the influence of family climate on the character building of students at SMAN 16 Pangkep, (3) the influence of the social studies learning process and family climate simultaneously to the character building of students at SMAN 16 Pangkep. This type of research descriptive quantitative. The population in this study were all students at SMAN 16 Pangkep amounts to which amounting 107 pearsons. The sampling technique in this research was using the technique of cluster random sampling, then taken samples of two classes were class 10 as many as 35 and class 11 as many as 28 pearsons. The technique collection of data used was the distributions of questionnaires and engineering documentation. The technique data analysis had been done by analyzing the results of the answers of respondents to the questionnaire using analysis descriptive in the form of percentage and analysis inferentially by using test requirements analysis and test hypotheses . The results of the study had demonstrated that: (1) there was a significant influence to the social studies learning process against the character building of students in class 10, while in class 11, there was no a significant influence to the social studies learning process against the character building of students at SMAN 16 pangkep, (2) there was a significant influence to the the climate family against the character building of students in class 10, while in class 11, there was no a significant influence to the the climate family against the character building of students at SMAN 6 Pangkep, (3) there was a significant influence to the social studies learning process and climate family were simultaneous against the character building of students in class 10, while in class 11, there was no a significant influence to the social studies learning process and climate family were simultaneous against the character building of students at SMAN 16 Pangkep .